Prevention And Treatment Of Pedophilia Based On The Psychospiritual Therapy Of The Quran And Sunnah: A Review Of Literature And Research Agenda - Tuan Ahmad Abrar Bin Tuan Makhtar; Mohd Zohdi Mohd Amin; Muhammad Fawwaz Muhammad Yusoff (Human Resource Management Academic Research Society, 2024)
Indexed by ERA